Factors affecting nutritional status of five years old children in Islamabad, Pakistan. - Shaikh, Fayyaz Ahmed (2007)
ABSTRACT: This cross-sectional study aimed to analyze the factors affecting the nutritional status of five year old children in Islamabad District, Pakistan from 11th January to 30thjanuary 2007. Two hundred mothers who were taking care of five year old children were interviewed and these children were measured for weight and height with the aims of finding maternal characteristics, children characteristics , maternal knowledge and practical factors affecting nutritional status of children. Epi info version 6 was used to analyze the data in terms of descriptive statistics. The result revealed that there was a high prevalence of malnutrition in the children (37%) in this area. The result indicated that low education of mothers was significantly related to a child's poor nutritional status(p-0.024). Other contributing factors were the childhood illness causing itching around the anus(saw pin worm) (p=0.023),low protein consumption(Beef) (p=0.031) and low daal 9p=0.0280 in regular meals. The result also showed that 50%of children of mothers who were working at other occupations were malnourished and parents where were more than six children in the family, 37% of were malnourished. Mothers who were living alone had more children with malnutrition ( 66.6%0 and children who were incompletely immunized had more chance got of malnutrition (40%). Also more girls were malnourished than boys. Based on these results, it is suggested that intervention strategies must be planned to stop this catastrophe immediately. The education system must be improved and improvement must be made to primary health care in the areas of groups at risk of malnutrition caused by illness, childcare, immunization and nutrition . Furthermore, problem solving should focus on discrimination between boys and girls, maternal education, occupation, marital status and provision of nutritious food. Key Words: factors affecting, Nutritional status, Children 5 years old